Naphthalene flanked diketopyrrolopyrrole: a new conjugated building block with hexyl or octyl alkyl side chains for electropolymerization studies and its biosensor applications. Issue 27 (12th June 2019) - Ponnappa, Supreetha Paleyanda; Liu, Qian; Umer, Muhammad; MacLeod, Jennifer; Jickson, Jospeh; Ayoko, Godwin; Shiddiky, Muhammad J. A.; O'Mullane, Anthony P.; Sonar, Prashant
Abstract : Naphthalene flanked DPP with hexyl and octyl chain based electropolymerized conjugated polymers exhibits bio-sensing. Abstract : Diketopyrrolopyrrole (DPP) is one of the most fascinating organic dyes, and has gained significant attention in the organic electronic community in recent times. Due to their outstanding semiconducting properties, DPP-based small molecules and polymers can be used as active semiconductor thin films for various high performance electronic devices. However, although several flanking groups attached to the DPP backbone have been reported in the literature for DPP molecules, there is little study about the effect of fused rings flanked on both sides of the DPP core. Recently our group reported for the first time a naphthalene-flanked DPP as a new DPP family member. In this work, we have performed electropolymerization studies on a newly synthesized naphthalene flanked DPP core with two alkyl chains, hexyl (H-DPPN ) and octyl (O-DPPN ), as conjugated monomers. Electrochemical studies have been carried out on glassy carbon (GC) and indium tin oxide (ITO) electrodes by using repetitive cyclic voltammetry (CV) as the deposition technique for up to 50 cycles. The concentration ofH-DPPN andO-DPPN solution in dichloromethane was found to be a key parameter when optimizing conditions for obtaining an electropolymerised thin film, although other parameters such as the electrolyte, potential range, number of cycles, and the nature of the electrode all play a role in successful thin film formation. The electropolymerized thin films were characterised using UV-Vis spectroscopy, atomic force microscopy (AFM), X-ray diffraction (XRD), X-ray photon spectroscopy (XPS) and surface profilometry. We found that each monomer produced different film morphologies on glassy carbon and ITO electrodes. We believe that electropolymerizedpoly(H-DPPN) andpoly(O-DPPN) thin film electrodes could be used for various applications such as studying redox reactions and bio-sensing.